EL RETORNO DEL ESTADO AUTORITARIO EN LA EDUCACIÓN SUPERIOR DEL ECUADOR - Granda Arciniega, Daniel (2024)
In this paper we analyze the trajectory of higher education in Ecuador, particularly the graduare doctoral level in their PhD during the last fifty years. We highlight sorne decisions of international law, especially on the graduate leve (and its influence on national legislation. We referenced the position of the State in its various moments in relation to higher education: At times the State is involved in the economy and the social life, but in higher education with precaution. Other times, the State relinguishes this aspect, resulting in neoliberalism, and the return of the authoritarian state in higher education occurs. In the lastest moment, we find the mythical conception of doctoral PhD, as part of techno-populist form of power. Also we displayed the situation of doctoral PhD at the Central University of Ecuador and its contribution to improving the quality of research, teaching, and participation in nacional development